2007
DOI: 10.1002/eji.200636636
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial clearance of Pseudomonas aeruginosa is enhanced by the inhibition of COX‐2

Abstract: Prostanoids generated by COX‐2 are involved in the regulation of inflammation but their exact role in the innate immune response has not been defined. We investigated whether COX‐2 is involved in host defense against Pseudomonas aeruginosa pneumonia. In vitro studies, in a macrophage cell line, showed that cytotoxic strain of P aeruginosa (PA103) induced significant COX‐2 protein expression and enzymatic function. In vivo data showed that infection with PA103 increased COX‐2 protein production in whole lung ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
118
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 40 publications
9
118
3
Order By: Relevance
“…A seminal study shows that PGE 2 inhibits the phagocytic activity of alveolar macrophage (70). In addition, PGE 2 suppresses production of reactive oxygen species (67). These results suggest that PGE 2 exacerbates Pseudomonas infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A seminal study shows that PGE 2 inhibits the phagocytic activity of alveolar macrophage (70). In addition, PGE 2 suppresses production of reactive oxygen species (67). These results suggest that PGE 2 exacerbates Pseudomonas infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pseudomonas lung infection also induces COX-2 expression in mice (67) and, as a result, produces not only PGD 2 but also other prostaglandins including PGE 2 (67,68). Increase of PGE 2 production in the lung is associated with bacterial pneumonia (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engagement of TLRs leads to activation of signaling pathways that results in generation of cytokines, chemokines, and lipid mediators produced by cyclooxygenases that are critical for host immune response (19,20). We and others have shown that activation of cyclooxygenase-2 (COX-2) and production of lipid mediators play a pivotal immunomodulatory role in fungal, viral, and bacterial infections (21)(22)(23)(24)(25). In particular, PGE 2 has immunosuppressive effects and impairs bacterial clearance (22,23,(26)(27)(28)(29), whereas PGD 2 has been shown to have immunostimulatory effects (30,31).…”
mentioning
confidence: 99%
“…It was previously reported that PGE2 signaling through EP2 aids in the survival of intracellular pathogens [14,15]. On the other hand, the results of Kaul et al [10] indicate that PGE2 signaling via EP2 is a host-protective pathway for M. tuberculosis infections.…”
mentioning
confidence: 99%